On a family of Euler-type numbers and polynomials - Claudio Pita-Ruiz (Rendiconti di Matematica e delle Sue Applicazioni, 2023)
We consider a family of Euler-type polynomials, depending on a real parameter α 6= 0, 1. The case α = 2 corresponds to standard Euler polynomials. We show some properties of these polynomials, and show also two generalized recurrences. As consequences of these results, we obtain several explicit formulas for Euler numbers and polynomials.